2019
DOI: 10.1021/acs.nanolett.9b04584
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Seed-Mediated Growth of Co Nanoparticles by the Polyol Process: Unraveling the Heterogeneous Nucleation

Abstract: The one-step seed-mediated synthesis is widely used for the preparation of ferromagnetic metal nanoparticles (NPs) since it offers a good control of particle morphology. Nevertheless, this approach suffers from a lack of mechanistic studies because of the difficulties to follow in real time the heterogeneous nucleation and to predict structure effects with seeds that are generated in situ. Here, we propose a complete scheme of the hetero-nucleation process involved in onepot seed-mediated syntheses of cobalt n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 60 publications
(129 reference statements)
1
29
0
Order By: Relevance
“…High‐resolution TEM (HRTEM) images in Figures c, S3a‐b show a highly crystalline Co branch that grows along the c ‐axis of a hcp structure, as indicated by the FFT pattern obtained from the core region of the branch (Figure S3c). Growth along the hexagonal c ‐axis is consistent with other rod‐like morphologies observed for hcp Co nanoparticles . The highly crystalline metallic Co can facilitate the electron transfer processes, contributing to higher activity .…”
Section: Resultssupporting
confidence: 84%
“…High‐resolution TEM (HRTEM) images in Figures c, S3a‐b show a highly crystalline Co branch that grows along the c ‐axis of a hcp structure, as indicated by the FFT pattern obtained from the core region of the branch (Figure S3c). Growth along the hexagonal c ‐axis is consistent with other rod‐like morphologies observed for hcp Co nanoparticles . The highly crystalline metallic Co can facilitate the electron transfer processes, contributing to higher activity .…”
Section: Resultssupporting
confidence: 84%
“…Contrary to the kinetic conditions involved in the early formation of spherical Co NPs, the nuclei were generated under thermodynamic conditions in an OAm.HCl and OAm texturized mixture inducing anisotropic regrowth. Interestingly, in the recent paper published by Viau et al (Scheme 1, green square), 22 the authors suggested that the released hydrogen may acted as a reductant in the reduction of cobalt at the surface of noble metal seeds. Our results developed in this publication, proved that the hydrogen in-situ generated allowed the reduction of cobalt salts.…”
Section: Discussionmentioning
confidence: 99%
“…13 The mechanistic aspects of the synthesis of the nanorods are not always clearly identified depending on the metal; [14][15][16] and, in the specific case of cobalt nanorods only two different mechanistic pathways have been reported: i) An Organometallic pathway (Scheme 1, orange square), with the reduction of coordinated cobalt complexes in presence of fatty carboxylic acid and amino ligands mixture under hydrogen pressure at 150°C, the proposed mechanism identified three main steps: a fast nucleation, then a fast growth with the reduction of cobalt complex and the epitaxial attachment of the nuclei completely formed through a slow ripping by the coalescence of NRs once the full reduction is completed; [17][18][19] and, ii) The Polyol process (Scheme 1, green square), with the reduction of cobalt carboxylate salts via a polyol process in presence of a small amount [RuCl3] or [IrCl3] (2.5%) and NaOH at 180°C, during the reaction, it was established that an initial formation of noble metal seeds, the nucleation step, is separated to a later reduction of cobalt precursors and induced a directed growth leading by the crystalline structure of the Ru/Ir seeds. [20][21][22] For the organometallic pathway and polyol process, the favorable adsorption of carboxylate ligand at the {112 $ 0} facets induce an easier attachment of cobalt nuclei along the c axis. 19,23 Additionally, an Oswald ripening may be required to increase the homogeneity of NRs.…”
Section: Introductionmentioning
confidence: 99%
“…We recently focused on the preparation of Co NPs using it. 27,28 By varying the preparation parameters, multiple shapes were obtained, like nanorods, 27,29,30 nanowires, 31 sea-urchinlike particles, 27 cubic particles, 27 hourglass-like particles 30 and platelets. 29,30 Combining experimental and periodic DFT investigations, we also rationalized the role of the carboxylate ligand in the shape control.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 By varying the preparation parameters, multiple shapes were obtained, like nanorods, 27,29,30 nanowires, 31 sea-urchinlike particles, 27 cubic particles, 27 hourglass-like particles 30 and platelets. 29,30 Combining experimental and periodic DFT investigations, we also rationalized the role of the carboxylate ligand in the shape control. 29 Changing its concentration in the growth solution tunes its chemical potential and hence the relative stability of decorated crystallographic surfaces, and thereby the shape of the Co NPs.…”
Section: Introductionmentioning
confidence: 99%